Exploring differences in smokers' perceptions of the effectiveness of cessation media messages. Issue 1 (18th September 2010) - Davis, Kevin C; Nonnemaker, James M; Farrelly, Matthew C; Niederdeppe, Jeff
Abstract : Objective: To examine which types of cessation-focused advertisements are associated with perceived advertisement effectiveness among smokers and to assess whether key smoker characteristics (ie, cigarette consumption, desire to quit and past quit attempts) influence perceived effectiveness of different types of cessation ads. Methods: We used data from the New York Media Tracking Survey Online, a web survey of 7060 adult smokers in New York. Participants were exposed to four categories of cessation ads: (1) why to quit—graphic images, (2) why to quit—testimonial, (3) how to quit and (4) anti-industry. Perceived ad effectiveness was measured with a four-item scale assessing the degree to which participants thought the ads made them stop and think, grabbed their attention, were believable and made them want to quit smoking. We categorised smokers based on cigarette consumption, desire to quit and past quit attempts. We used multivariable analyses to examine how smoker characteristics and category of cessation ads predict perceived ad effectiveness. Results: Ads using the 'why to quit' strategy with either graphic images or personal testimonials were perceived as more effective than the other ad categories. Smokers who had less desire to quit or had not tried quitting in the past 12 months responded significantly less favourably to all types of cessation ads tested. Greater cigarette consumption was also associated with lower perceived effectiveness, but this association was smaller in magnitude. Conclusions: Tobacco control programmes that utilise cessation-focus advertising should focus relatively more on ads that adopt the 'why to quit' strategy with either graphic images or personal testimonials.